Potential of Electrospun Fibrous Scaffolds for Intestinal, Skin, and Lung Epithelial Tissue Modeling. Issue 4 (27th January 2023) - Gonçalves, Andreia M.; Leal, Filipa; Moreira, Anabela; Schellhorn, Tobias; Blahnová, Veronika Hefka; Zeiringer, Scarlett; Vocetková, Karolina; Tetyczka, Carolin; Simaite, Aiva; Buzgo, Matej; Roblegg, Eva; Costa, Pedro F.; et al.
Abstract : Herein, intestinal, skin, and pulmonary in vitro tissue models based on electrospun membranes of poly(ε‐caprolactone) (PCL) and cellulose acetate (CA), cellulose acetate phthalate (CAP), ethylcellulose (EC), or methylcellulose (MC) are presented. Physicochemical characterization and biocompatibility analyses of the scaffolds are carried out using colorectal adenocarcinoma cells (intestine), keratinocytes and fibroblasts (skin), and bronchial and alveolar epithelial cells (lung). PCL, PCL:CA, and PCL:EC are composed of nanofibers, whereas PCL:CAP and PCL:MC scaffolds comprise a combination of micro‐ and nanofibers. PCL, PCL:CA, PCL:CAP, and PCL:EC samples demonstrate water contact angles greater than 90° and are, therefore, hydrophobic, while PCL:MC mats display a hydrophilic behavior. In intestinal models, cells adhere and proliferate on all scaffolds; in turn, studies with skin cell models reveal that PCL:CA and PCL:CAP blends outperform all other substrates. Lung cell models show that, while 16HBE cells adhere to and proliferate in PCL, PCL:CA, PCL:EC, and PCL:MC scaffolds, A549 cells only have the same biological response on PCL, PCL:CA, and PCL:MC. In summary, all fibrous meshes prepared are biocompatible toward most cell types tested, thus suggesting the potential of PCL‐cellulose derivative blends as substrates suitable for in vitro epithelial tissue modeling and toxicity screening. Abstract : Herein, the potential of different electrospun fibrous scaffolds for intestinal, skin, and lung in vitro tissue modeling is investigated. Electrospun membranes of poly(ε‐caprolactone), cellulose acetate (CA), cellulose acetate phthalate (CAP), ethylcellulose (EC), or methylcellulose (MC) are synthesized and physicochemically characterized, followed by biocompatibility analyses with epithelial cell lines. All fibrous meshes prepared are biocompatible, with cell‐specific differences.